Comparative proteomics analysis of tea leaves exposed to subzero temperature: Molecular mechanism of freeze injury - Yongguang, Hu; Yongzong, Lu; Jian, Lu (International Journal of Agricultural and Biological Engineering, 2013)
Abstract: Tea freeze injury is one of the most severe agro-meteorological disasters, which leads to sizable losses of tea production in China. The freezing resistant ability of overwintering tea trees becomes weaker and weaker from early-spring to late-spring. If it decreases to critical temperature of -2 ℃ or lower in the stage with one or two leaves, tea trees suffer from freeze injury and the yield or quality of spring tea production could decrease greatly. Although measurements have been taken to prevent such damage, the physiological and biochemical mechanism of how tea (Camellia Sinensis) plant response to freeze injury is still to be elucidated. A comparative proteomics analysis was made on tea leaves at the two-leaf stage. The differential image analysis showed 46 spots with density changes (29 spots increased and 17 spots decreased; p<0.01) in the freeze injury group compared with the control group. Thirty eight differential protein spots (p<0.01) with good resolution and relatively high abundance in MS were subjected to further protein identification. Among them, all 17 up-regulated spots were collected whereas only six of the down-regulated spots were selected. These differentially expressed proteins including heat shock protein 70, oxygen-evolving enhancer protein, adenosine triphosphate synthase, S-adenosylmethionine synthetase and some enzymes involved in carbohydrate metabolism, were shown responsive to freeze injury. The results would greatly increase the comprehension of the molecular mechanism for freeze injury and provide a better decision making for freeze protection and control.Keywords: freeze injury, molecular mechanism, freeze protection, comparative proteomics, Camellia Sinensis, mass spectrometryDOI: 10.3965/j.ijabe.20130604.004Citation: Hu Y G, Lu Y Z, Lu J. Comparative proteomics analysis of tea leaves exposed to subzero temperature: Molecular mechanism of freeze injury. Int J Agric & Biol Eng, 2013; 6(4): 27－34.